Pengaruh Kepemimpinan Kepala Madrasah dan Profesionalitas Guru terhadap Hasil Belajar Peserta Didik untuk Mata Pelajaran Fiqih di MI Mathla’ul Huda Babakan 02 - Sastrajaya Sastrajaya; Muhammad Jaenudin; Gunawan Anjar (Jurnal Dirosah Islamiyah, 2023)
The improvement of student learning outcomes at MI Mathla'ul Huda Babakan 02 is supported and influenced by various factors, both external and internal students. These factors include the leadership factor of the head of the madrasa and the factor of teacher professionalism at MI Mathla'ul Huda Babakan 02. The purpose of this study is to determine 1) the influence of madrasah head leadership on student learning outcomes, 2) the influence of teacher professionalism on student learning outcomes, and 3) the influence of madrasah head leadership and teacher professionalism together on student learning outcomes at MI Mathla'ul Huda Babakan 02. The results showed that the teacher's professionalism variables were more dominant in influencing the learning outcomes of students than the leadership variables of madrasah heads. This is evident from the results of the determination test showing that the correlation and determination variables of rhitung teacher professionalism were 39.6% and R2 was 0.396, while for the leadership variables of the head of the rhitung madrasah was 32.6% and R2 was 0.326. Keywords: madrasa head leadership, teacher professionalism, learner learning outcomes